The Chemistry of Cu3N and Cu3PdN Nanocrystals. Issue 31 (15th June 2022) - Parvizian, Mahsa; Duràn Balsa, Alejandra; Pokratath, Rohan; Kalha, Curran; Lee, Seungho; Van den Eynden, Dietger; Ibáñez, Maria; Regoutz, Anna; De Roo, Jonathan
Abstract: The precursor conversion chemistry and surface chemistry of Cu3 N and Cu3 PdN nanocrystals are unknown or contested. Here, we first obtain phase‐pure, colloidally stable nanocubes. Second, we elucidate the pathway by which copper(II) nitrate and oleylamine form Cu3 N. We find that oleylamine is both a reductant and a nitrogen source. Oleylamine is oxidized by nitrate to a primary aldimine, which reacts further with excess oleylamine to a secondary aldimine, eliminating ammonia. Ammonia reacts with Cu I to form Cu3 N. Third, we investigated the surface chemistry and find a mixed ligand shell of aliphatic amines and carboxylates (formed in situ). While the carboxylates appear tightly bound, the amines are easily desorbed from the surface. Finally, we show that doping with palladium decreases the band gap and the material becomes semi‐metallic. These results bring insight into the chemistry of metal nitrides and might help the development of other metal nitride nanocrystals. Abstract : Phase‐pure, colloidally stable Cu3 N and Cu3 PdN were obtained. The precursor conversion mechanism is elucidated; oleylamine is oxidized to a primary aldimine and the latter reacts further with oleylamine to a secondary aldimine, eliminating ammonia. Ammonia reacts with Cu I to form Cu3 N.